Dinamika Perkembangan Batas Usia Perkawinan Dalam Perspektif Hukum Progresif - Muhammad Jazil Rifqi (Arena Hukum, 2022)
This article aims to explore the development of the minimum age for marriage in Indonesian legislation and analyze it with progressive law. To explain the transformation of law, this literature research uses a social history approach. This study found that the embryonic age limit for marriage had actually been seen in legal pluralism before the enactment of the 1974 Marriage Law. The marriage age in the Marriage Law Number 1 of 1974 was stated to be 16 years for women and 19 years for men. Unfortunately, the regulation was not in line with the development of society, so it was tested in the Constitutional Court. In 2017, article 7 paragraph (1) was examined where the Constitutional Court granted the request by equating the marriage age to 19 years for men and women. The House of Representatives then amended the Marriage Law as contained in Law Number 16 of 2019. This reform illustrates that the law is not final and absolute, under certain conditions as long as it provides benefits for humans, it is necessary to revise the law. Not vice versa, allowing people to enter into legal schemes that have a negative impact on health, education, economy and so on, but laws that must be studied and corrected.